Post Joyful Learning: An Alternative in Post Pandemic Era - Wildan Adrikal Amin Nabil; Kiswati (ELITE JOURNAL, 2023)
ABSTRACTPost pandemic era pushes education system to adjust the situation. After corona virus problem has gone doesn’t mean we can live normal like before pandemic. Teachers and students were forced to use technology and did online learning during pandemic. Schools that forbid students to bring handphone and other gadgets suddenly had to use all of them because they had to do distance learning. Some researchers found that most online learning failed to increase the students’ achievement because without the existence of teachers in the learning proses won’t be meaningful. This article is report of a two-cycle classroom action research conducted in MAN 5 Jombang during the implementation of practice teaching of UIN Maliki student. He used post joyful learning strategy in teaching grammar. The method was used both conventional and technology used in adapting to the post pandemic era. It was found that the grammar score of the students improved significantly from preliminary study to cycle 2. The students’ motivation during the learning process was also improved. It can be concluded that the use of post joyful learning strategy can improve the students’ grammar mastery. Keywords: Post Pandemic; Grammar Mastery; Post Joyful Learning